2022
DOI: 10.1259/bjr.20210779
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced digital breast tomosythesis and breast MRI to monitor response to neoadjuvant chemotherapy: patient tolerance and preference

Abstract: Objectives: Contrast-enhanced digital breast tomosynthesis (CE-DBT) is a novel imaging technique, combining contrast-enhanced spectral mammography (CESM) and tomosynthesis. This may offer an alternative imaging technique to breast MRI for monitoring of response to neoadjuvant chemotherapy. This paper addresses patient experience and preference regarding the two techniques. Methods: Conducted as part of a prospective pilot study; patients were asked to complete questionnaires pertaining to their experience of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Although not the focus of this study, we demonstrated through patient feedback questionnaires, a high acceptance of CEM+DBT as an imaging technique and a preference for it compared with CE-MRI. 15 This further supports the feasibility of CEM+DBT as a treatment monitoring modality.…”
Section: Discussionsupporting
confidence: 60%
“…Although not the focus of this study, we demonstrated through patient feedback questionnaires, a high acceptance of CEM+DBT as an imaging technique and a preference for it compared with CE-MRI. 15 This further supports the feasibility of CEM+DBT as a treatment monitoring modality.…”
Section: Discussionsupporting
confidence: 60%
“…As a technique it is more time-efficient and often preferred by patients. [11][12][13] Furthermore, switching to CESM would reduce the pressure on MRI services for other imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence from three studies of between 18 and 49 participants, demonstrates patient preference for CESM over MRI. 1113 This adds further weight to the argument that it may be appropriate to use CESM instead of MRI for loco-regional staging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that CEM has high specificity and sensitivity, and may have broader prospects in evaluating the response to neoadjuvant therapy [ 9 ]. However, CEM also has limitations, such as anaphylaxis and extravasation of contrast agents, increased radiation dose during multiple evaluations of response to neoadjuvant breast cancer, and inability to fully evaluate axillary lymph nodes and display lesions close to the chest wall or the medial breast [ 10 ].…”
Section: Introductionmentioning
confidence: 99%